2021
DOI: 10.1021/acs.macromol.1c01427
|View full text |Cite
|
Sign up to set email alerts
|

“Tying the Knot”: Enhanced Recycling through Ultrafast Entangling across Ultrahigh Molecular Weight Polyethylene Interfaces

Abstract: Ultrahigh molecular weight polyethylene (UHMWPE) is a high-end engineering polymer. However, the very features that lead to its exceptional properties, i.e., ultralong macromolecular chains, render joining two surfaces of this material a tedious and slow process, leading to long welding times and impeding mechanical recycling of UHMWPE.Here we report the anomalous fast joining of UHMWPE interfaces by simply depositing small amounts of nascent disentangled UHMWPE powder at the interface. The time evolution of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…This could be improved by the addition of a coloring agent to color the powder so that the wavelength of the laser can be absorbed by it. Lastly, for the case of UHMWPE processed through SLS, good adhesion between the powder particles could be achieved by using disentangled UHWMPE powder that has been shown to rapidly re-entangle upon melting, through a mechanism that deviates from slow reptation kinetics [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be improved by the addition of a coloring agent to color the powder so that the wavelength of the laser can be absorbed by it. Lastly, for the case of UHMWPE processed through SLS, good adhesion between the powder particles could be achieved by using disentangled UHWMPE powder that has been shown to rapidly re-entangle upon melting, through a mechanism that deviates from slow reptation kinetics [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 For a molecular chain explanation, it was discovered via neutron scattering tests that the mean square radius of gyration increases abnormally during melting, de Gennes calls them "chain explosion" or "melting explosion". 16,19 The melting explosion should be a special type of melting of very highly regularized UHMWPE crystals. Current research has focused on the utilization of this phenomenon to promote instantaneous adhesion between UHMWPE surfaces and interparticle welding efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Current research has focused on the utilization of this phenomenon to promote instantaneous adhesion between UHMWPE surfaces and interparticle welding efficiency. Recent research on autoadhesion during sintering has shown that nascent commercial UHMWPE is also capable of melting explosion and is critical for the success of sintering. ,, It is usually accepted that the diffusion distance of chains during healing is related to only temperature and time. However, the melting explosion shows that the chain diffusion is also closely related to melting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to these properties changes, the applications of the mechanically recycled polymers have to be adapted [10][11][12]. Whereas the majority of recycled high and low-density polyethylenes (HDPE and LDPE) are however produced that way, Ultra High Molecular Weight Polyethylenes (UHMWPE), mostly used for high-performance applications due to their superior mechanical properties, are more difficult or impossible to process due to their high viscosity [13]. The other principal way of recycling polymers is by chemical recycling, which consists of a chemical transformation leading to new raw materials.…”
Section: Introductionmentioning
confidence: 99%